Recreational Evaluation of Water Resources Near the City - Hilal Surat (Megaron, 2019)
Deriner Dam and its surroundings; geographical location, morphological characteristics, climate, vegetation cover, traditional cultural features and diversity, has an important potential for recreational purposes. Deriner dam lake which has a reconstructed physical structure and its surrounding firstly, the current situation should be put forward natural, cultural and historical richness of both recreational and tourism aspects of the use, promotion and ecological continuity. For this purpose, SWOT analysis was performed to reveal the current situation. Then, AHS technique was used to determine the strategies for the development and effective use of the factors resulting from SWOT analysis. As a result of SWOT analysis has been put forward, 9 strengths, 7 weaknesses, 9 opportunity opportunities and 4 threat elements of Deriner Dam Lake and surrounding. Considering these SWOT analysis results, 3 main and 7 sub-strategies were determined.